Ill effects of smoking on general and oral health: Awareness among college going students - Yash Paul; Nitin Soni; Rohit Vaid; P Basavaraj; Nitin Khuller (Wolters Kluwer Medknow Publications, 2014)
Purpose: This cross-sectional study assessed smoking-related behaviors, experiences, beliefs, knowledge, and prevalence among a sample of college going students. It helped to inform them about the different nicotine replacement therapies (NRTs) available for the cessation of the habit. Materials and Methods: After gaining informed consent, 500 college going students (18-25 years age group) of Swami Devi Dyal Group of Colleges, who are smokers and also willing to participate in the study were surveyed regarding their awareness about and prevalence of ill effects of smoking. The survey was conducted by employing a uniform questionnaire. The questionnaire assessed about the tobacco use, no of cigarettes they smokes every day, what form of smoking do they prefer, early smoking experiences and sensations, factors that might motivate a quit attempt, ill effects of smoking on oral health, other psychosocial variables associated with adolescent smoking and about the different NRTs available. The feedback hence obtained was condensed in the form of objective results, which were analyzed to arrive at meaningful conclusions. Results and Conclusion: According to the study as many as about 90% of the students have reasonably good chances of succeeding in quitting smoking. However, the overwhelming majority (96%) had no idea about different NRTs. This shows a stark lack of awareness as to the means that can help them quit the habit. Thus, we get a clear vision as to the direction of our efforts and feel optimistic as to the outcome too.